Kebijakan Legislatif tentang Pidana Denda dan Penerapannya dalam Upaya Penanggulangan Tindak Korupsi - Syaiful Bakhri (Fakultas Hukum Universitas Islam Indonesia, 2010)
This research focuses the issue of legislative policy of fine and its implementation in effort to overcome corruption. By using normative and qualitative legal method, this research revealed the following facts. First, implementation of fine in positive law of Indonesia not accordance with the punishment objectives as regulated in Criminal Act besides Indonesian Civil Code. In fact, fine seems like ineffective sanction. So, even though there are lots regulation about fine which mostly imposing high fine to defender, but it cannot creates preventive and deterrence effect. Second, effectiveness of fine implementation in court practice still questionable. In corruption case, sometime judges imposed high imprisonment to offender and supplemented with lower fine. In imposing fine, mount of fine is under the minimum standard which regulated in Corruption Act. Third, fine must be formulated with rational, exact and efficient ways. Related with the effort to overcome corruption, fine must be maximized to punish offender to achieve deterrence effect.Key words : Fine, corruptions, legislatife policy